AFM as an analysis tool for high-capacity sulfur cathodes for Li–S batteries - Hiesgen, Renate; Sörgel, Seniz; Costa, Rémi; Carlé, Linus; Galm, Ines; Cañas, Natalia; Pascucci, Brigitta; Friedrich, K. Andreas (Beilstein Journal of Nanotechnology, 2013)
In this work, material-sensitive atomic force microscopy (AFM) techniques were used to analyse the cathodes of lithium–sulfur batteries. A comparison of their nanoscale electrical, electrochemical, and morphological properties was performed with samples prepared by either suspension-spraying or doctor-blade coating with different binders. Morphological studies of the cathodes before and after the electrochemical tests were performed by using AFM and scanning electron microscopy (SEM). The cathodes that contained polyvinylidene fluoride (PVDF) and were prepared by spray-coating exhibited a superior stability of the morphology and the electric network associated with the capacity and cycling stability of these batteries. A reduction of the conductive area determined by conductive AFM was found to correlate to the battery capacity loss for all cathodes. X-ray diffraction (XRD) measurements of Li2S exposed to ambient air showed that insulating Li2S hydrolyses to insulating LiOH. This validates the significance of electrical ex-situ AFM analysis after cycling. Conductive tapping mode AFM indicated the existence of large carbon-coated sulfur particles. Based on the analytical findings, the first results of an optimized cathode showed a much improved discharge capacity of 800 mA·g(sulfur)−1 after 43 cycles.
Keywords: conductive AFM; high capacity; lithium-sulfur batteries; material-sensitive AFM; sulfur cathode